Microstructure, Piezoelectric and Dielectric Properties of Lead-Free Ceramics K0.475Na0.475Li0.05NbO3-CaZrO3-CuO - Li, Shaobo; Yin, Qiyi; Tian, Changan; Yang, Benhong; Xie, Jinsong; Bao, Meiling (Asian Journal of Chemistry, 2013)
The (1-x)K0.475Na0.475Li0.05NbO3-xCaZrO3-2 % molCuO lead-free piezoelectric ceramics have been prepared by conventional technique at 1140 ºC and exhibit highly dense structure by SEM patterns observed. X-ray diffraction analysis shows that the ceramics possess a pure perovskite structure and only have tetragonal phases. The ceramic with x = 0.045 possess optimum electrical properties (d33 = 176 pC/N, kp = 37 %, er = 1083, tan d = 2.4 %). This results indicate that the ceramic is a promising lead-free piezoelectric ceramic.